Implementasi Metode K-Nearest Neighbor dalam Menentukan Waktu Optimal Penarikan Pesanan Driver Ojol - Prasetiyo, Anton (Universitas Multi Data Palembang, 2024)
App-based transportation companies are propelling technological advancements in the services provided to every user and online motorcycle taxi partner. Online motorcycle taxis currently represent the most popular and widely used mode of transportation. Thanks to the application system's ability to enable online motorcycle taxi partners to work from anywhere and at any time, an increasing number of individuals are expressing interest in becoming such partners. However, this surge in interest has led to new challenges, particularly regarding income from orders within the competitive landscape of online motorcycle taxi partnerships. Therefore, the author aims to address these issues through this research. Classification algorithms are employed to analyze the optimal timing for processing order requests. This study seeks to develop a classification model using the K-Nearest Neighbor method to determine the optimal timing based on label classes. K-Nearest Neighbor involves identifying k target members in the training data closest to the target in the testing or new data. The dataset utilized in this research is sourced from three online motorcycle taxi driver accounts, comprising a total of 1941 datasets. The classification results using the K-Nearest Neighbor method yielded excellent outcomes, achieving an accuracy level of 99%. Subsequently, testing with a value of k=9 and an 80:20 ratio resulted in an average f1-score of 99.33%.